Wordwall in the classroom: A qualitative study of student-teacher perspectives - Fonna, Febiza; Adani, Sukri (Journal of Research in Instructional, 2025)
Wordwall is a digital platform that enables educators to create various interactive learning activities. This study explored the perceptions of students as instructors regarding the use of Wordwall in Kampus Mengajar program in Southwest Aceh. This study was conducted to identify the problems related to whether Wordwall was effective as an innovative learning media and to find out the challenges faced in its implementation at elementary schools in Southwest Aceh. Data collection was conducted using a qualitative method, specifically in-depth interviews with 10 student participants of Kampus Mengajar batch 8 in Southwest Aceh who used Wordwall. Thematic analysis was used to process interview data and help identify main themes and categories from interview transcripts. The results showed that Wordwall increased students' motivation, participation, and understanding, as well as created a fun interactive learning atmosphere. The challenges faced included internet connection issues, limitations of devices and access, and unfamiliarity with the digital platform. For future research, it was recommended to conduct a quantitative study with a larger sample size and to involve teachers and students directly in order to obtain a more comprehensive understanding of the effectiveness of Wordwall in improving learning outcomes and addressing technical challenges in various school contexts.